1996
DOI: 10.1111/j.1476-5381.1996.tb15188.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation of 5‐HT1‐like and 5‐HT2A receptors in the contraction of human temporal artery by 5‐hydroxytryptamine and related drugs

Abstract: 1 We investigated the hypothesis that, as in some other large human arteries, 5-HT-induced contraction of the temporal artery is mediated through two co-existing receptor populations, 5-HT,-like-and 5-HT2A. Temporal arterial segments were obtained from patients undergoing brain surgery and rings prepared set up to contract with 5-HT and related agents. 2 In rings with intact endothelium 5-HT evoked contractions with a -log EC50, M of 7.0. Ketanserin (10-1000 nM) antagonized part of the 5-HT-induced contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…For uterine artery and saphenous vein the sumatriptan response was smaller (< 50% relative to 5‐HT) indicating the involvement of both 5‐HT 1B ‐receptors and a larger 5‐HT 2 ‐receptor component [5]. In contrast in temporal artery, sumatriptan was a weak vasoconstrictor consistent with the absence of 5‐HT 1B ‐receptor immunoreactivity [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For uterine artery and saphenous vein the sumatriptan response was smaller (< 50% relative to 5‐HT) indicating the involvement of both 5‐HT 1B ‐receptors and a larger 5‐HT 2 ‐receptor component [5]. In contrast in temporal artery, sumatriptan was a weak vasoconstrictor consistent with the absence of 5‐HT 1B ‐receptor immunoreactivity [4].…”
Section: Discussionmentioning
confidence: 99%
“…5‐HT receptors can be classified in 14 distinct subtypes and 5‐HT 1 ‐, 5‐HT 2 ‐ and 5‐HT 7 ‐receptors have been demonstrated to mediate changes in vascular tone [1]. 5‐HT 7 ‐receptor activation causes vasorelaxation [2, 3], whereas 5‐HT 1B/1D ‐receptors and/or 5‐HT 2A ‐receptors, which are negatively linked to adenylate cyclase, mediate vasoconstriction [4–6]. 5‐HT 1F ‐receptors are also negatively coupled to adenylate cyclase [1] and mRNA coding for this receptor subtype is expressed in vascular smooth muscle cells, however, activation of this receptor does not directly influence vascular tone [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently proposed that 5‐hydroxytryptamine (5‐HT) contracts human temporal artery through both 5‐HT 1‐like receptors and 5‐HT 2A receptors (Verheggen et al , 1996). Sumatriptan also caused contractions through 5‐HT 1‐like receptors but not 5‐HT 2A receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The 5‐HT like receptors that mediate contraction could correspond either to the recombinant 5‐HT 1B (ex 5‐HT 1Dβ ) receptor or to the recombinant 5‐HT 1D (ex 5‐HT 1Dcα ) receptor (as reviewed by Hoyer et al , 1994; Hartig et al , 1996); both display a remarkably similar pharmacology (as reviewed by Kaumann et al , 1993). Verheggen et al (1996) suggested that the 5‐HT 1‐like receptors of temporal artery were more likely to be 5‐HT 1B than 5‐HT 1D , due to the failure of ketanserin to cause blockade at 1 μM, a concentration that would be expected to block 5‐HT 1D receptors but not 5‐HT 1B receptors (Kaumann et al , 1994).…”
Section: Introductionmentioning
confidence: 99%
“…UK, unknown receptor mechanism. Data were collected from the following references: Lemberger et al, 1984;Miller et al, 1984;Feniuk et al, 1985;Nyborg and Mikkelsen, 1985;Cohen, 1986;Leff et al, 1987;Hamel et al, 1989Hamel et al, , 1993Parsons et al, 1989Parsons et al, , 1992Bodelsson et al, 1990;Borton et al, 1990;Chester et al, 1990;Gaw et al, 1990;Mylecharane, 1990;Toda and Okamura, 1990;van Heuven-Nolsen et al, 1990;Asher et al, 1991;Lai et al, 1991;Parsons, 1991;Sumner, 1991;Cohen, 1992a,b, 1993;Dorigo et al, 1992;Eglen et al, 1992;Weiner et al, 1992;Bax et al, 1993;Glusa and Mü ller-Schweinitzer, 1993;Jansen et al, 1993;Cushing et al, 1994Cushing et al, , 1996Yildiz and Tuncer, 1994;Fujiwara and Chiba, 1995;Miranda et al, 1995;Schmuck et al, 1996;Terrón, 1996;Valentin et al, 1996;Verheggen et al, 1996Verheggen et al, , 1998Verheggen et al, , 2004Verheggen et al, , 2006Zwaveling et al, 1996;…”
Section: Figmentioning
confidence: 99%